Iowa RBA, March 25, 1996 - Fuller, James Let al; Iowa Ornithologists' Unionet al (1996)
Iowa RBA update for March 25, 1996. Highlights of the update include sightings of Glaucous Gulls, Lesser Black-backed Gulls and Sandhill Cranes. Also included are handwritten notes for the next week's update with sightings of a Baird's Sandpiper and an extremely early Buff-breasted Sandpiper. Epson - sheet feed/flatbed